Pembelajaran matematika secara daring pada masa pandemi Covid-19: efektivitas pembelajaran daring di SMK Negeri 2 Tanah Putih - Aulia, Jannatul; Roza , Yenita; Maimunah, Maimunah (Jurnal Math Educator Nusantara: Wahana Publikasi Karya Tulis Ilmiah di Bidang Pendidikan Matematika, 2021)
During the Covid-19 pandemic, the learning process must be carried out online. During the implementation of learning, it is undeniable that there are many complaints from various parties, especially students who judge online learning to be less effective. This study is a qualitative research with a descriptive method that aims to provide an overview of the effectiveness of online-based mathematics learning carried out at SMKN 2 Tanah Putih during the Covid-19 pandemic. The data collection technique was carried out using a google form questionnaire "Analysis of the implementation of online-based mathematics learning" with research subjects as many as 10 male students and 10 female students in class XI at SMKN 2 Tanah Putih. The data analysis used is descriptive statistics using the Miles & Huberman analysis model which consists of three stages, namely data reduction, data display, and conclusion drawing and verification. The results showed that the implementation of online learning in mathematics subjects at SMKN 2 Tanah Putih was categorized as less effective with an effectiveness level of 59.4%. Less effective learning is caused by factors that affect the online learning at SMKN 2 Tanah Putih which can be seen in technical indicators and implementation of learning.